Anatomy and relationships of the South African gorgonopsian Arctops (Therapsida, Theriodontia). (17th September 2017) - Kammerer, Christian F.
Abstract: The gorgonopsian genus Arctops from the late Permian of South Africa is revised and redescribed. The nominal species Arctops kitchingi and Arctops watsoni are found to be junior synonyms of the type species Arctops willistoni . A well‐prepared specimen previously referred to Lycaenops angusticeps and additional, previously undescribed specimens are also referred to A . willistoni . The vomerine morphology of Arctops is highly distinctive, supporting previous work highlighting the taxonomic importance of this element. Arctops is restricted to the Cistecephalus Assemblage Zone of the South African Beaufort Group. Inclusion of Arctops in a phylogenetic analysis of gorgonopsian relationships recovers it as the sister‐taxon of Smilesaurus ferox, with the clade composed of Arctops + Smilesaurus positioned outside the Rubidgeinae.